(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
The rapid digitization of U.S. social, economic, and healthcare systems has made digital participation a structural requirement for equitable access to services, employment, and health. Yet Not-for-Profit (NFP) organizations the frontline delivery system for community-based digital inclusion programs face deep structural constraints: capital scarcity, understaffed teams, and an almost total absence of technical infrastructure. These constraints render the traditional asset-heavy technology model not merely inefficient, but fundamentally unsustainable. This paper introduces Connected Technology as a Solution (CTaaS) a managed-service paradigm governed by a closed-loop 6S Lifecycle Framework: Sourcing, Stocking, Staging, Supply, Support, and Sustainability. Drawing on real-world evidence from senior home-health initiatives (Project Silver Echo) and youth workforce programs (Project Horizon), we demonstrate that CTaaS reduces device abandonment from over 40% to below 5%, raises RPM data continuity to 98.5%, and measurably improves workforce readiness. By converting technology from a depreciating asset into a predictable operational subscription, CTaaS aligns with grant funding structures, reduces total cost of ownership, and produces a compelling social return on investment. The result is a national-scale impact model that is simultaneously more affordable, more effective, and more sustainable than any predecessor approach.